Controlled weakening of model ice: Replicating the mechanical response of summer-warmed sea ice in laboratories and test basins - N. Fuchs; F. von Bock und Polach; P. Buil; S.M. Isay; D. Notz; L. Nupnau; N. Reimer; L. Schoepflin; T. Zorn (Ocean Engineering, 2026)

Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

The elephant in the room is really a cow: using consumption corridors to define sustainable meat consumption in the European Union - Miriam Cué Rio; Bernice Bovenkerk; Jean-Christophe Castella; Daniel Fischer; Richard Fuchs; Minna Kanerva; Mark D. A. Rounsevell; Nicolas Salliou; Eric O. Verger; Elin Röös (Sustainability Science, 2026)
Implementing the European Green Deal requires a consistent food systems’ policy that involves not only targeting the supply side but also conducting extensive changes in diets at the consumer level. Reducing meat consumption is an obvious strategy to put the European food system on track to meet the Green Deal’s goals. This cannot be achieved by focusing solely on consumer choice and individual responsibility. Stronger governance is required to reduce the scale of meat consumption to sustainable levels. Such governance needs to be informed by a holistic definition of “sustainable meat consumption”, designed to ensure that important sustainability priorities are not neglected, and to account for all emissions associated with EU consumption, regardless of where production takes place. This article presents a conceptual framework to define “sustainable meat consumption” based on the concept of consumption corridors (CCs). A CC is the space between a minimum (the floor) and maximum (the ceiling) consumption level, which allows everybody to satisfy their needs without compromising others’ ability to meet their own. Embedded in a powerful set of principles (recognizing universal needs; tackling both over and under-consumption; framing food as a common good; promoting public participation; and addressing environmental justice and planetary sustainability), CCs are attuned to the Green Deal’s ambition to “leave no one behind”, in the EU and beyond. CCs provide a demand-side solution encompassing a more equitable alternative to discuss what is actually a “fair share” of the world’s limited resources when it comes to meat consumption.

Bumblebees (Bombus terrestris) forage on plants treated with glyphosate-based herbicides despite potential behavioral consequences - Kimmo Kaakinen; Satu Ramula; Benjamin Fuchs; James D. Blande; Eva-Maria Vaajamo; Marjo Helander (Environmental Research, 2025)

Plankton communities today and tomorrow—potential impacts of multiple global change drivers and marine heatwaves - Cédric L. Meunier; Josefin Schmidt; Antonia Ahme; Areti Balkoni; Katharina Berg; Lea Blum; Maarten Boersma; Jan D. Brüwer; Bernhard M. Fuchs; Luis Gimenez; Maïté Guignard; Ruben Schulte‐Hillen; et al. (Limnology and Oceanography, 2025)
In the context of global change, marine organisms are subjected not only to gradual changes in abiotic parameters, but also to an increasing number of extreme events, such as heatwaves. However, we still know little about the influence of heatwaves on the structure of marine communities, and experimental studies are needed to test the impact of heatwaves alone and in combination with other environmental drivers. Here, we conducted a mesocosm experiment to assess the potential impact of heatwaves on plankton communities, which we did under ambient and future environmental conditions. To simulate future environmental conditions, we simultaneously manipulated temperature and pH based on IPCC predictions for 2100, and dissolved N : P ratios based on the conditions expected in European coastal zones. While we did not observe any effects of simulated heatwaves on phytoplankton abundances, we identified that future environmental conditions may favor smaller phytoplankton species and that additional heatwaves may especially favor small phytoflagellates and coccolithophores. We also observed that future environmental conditions may reduce the abundances and modify the species composition of bacterioplankton, microzooplankton, and mesozooplankton, and that heatwaves may exacerbate these effects. Using a unique approach to examine the potential impacts of heatwaves under current and future environmental conditions on a natural multi‐trophic marine plankton community, we show that the combination of multiple global change drivers has the potential to perturb the entire basis of marine food webs.

Chemical recycling of refrigerator plastic waste by pyrolysis: Yields, product composition, and potential applications - Jonas Vogt; Axel D. Renno; Margret Fuchs; Tim Kurtz; Niklas Netsch; Frank Richter; Grazyna Straczewski; Britta Bergfeldt; Yuleika Carolina Madriz-Diaz; Andréa de Lima Ribeiro; Doreen Ebert; Salar Tavakkol; et al. (Fuel, 2025)

Decode-STS: Deciphering the landscape of canine soft-tissue sarcoma using spatially defined proteomics and transcriptomics - D. Fuchs; E. Markkanen; H. Ech-Cherif; S. Aghaabbasi; A. Pöschel; E. Beebe; L. Laura; W. Wolski; F. Guscetti; M. Nolff (Journal of Comparative Pathology, 2025)

Antibacterial Synergism of Fluoxetine and Paroxetine with Ceftriaxone, Plasmid DNA Cleavage and Repositioning - Vitória S. Foletto; Marissa B. Serafin; Augusto D. da Mota; Taciéli F. da Rosa; Angelita Bottega; Sara L. Marion; Bruno R. de Paula; Laísa N. Franco; Luana B. Fuchs; Rosmari Hörner (Current Microbiology, 2025)

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Contrasting Population Trajectories of Temperate Reef Fishes and Invertebrates Following Seasonal and Multi‐Decadal Temperature Change - Yann Herrera Fuchs; Graham J. Edgar; Neville S. Barrett; Lara Denis‐Roy; Shenae Y. Willis; Hunter Forbes; Rick D. Stuart‐Smith (Global Change Biology, 2025)
Temperature perturbations from climate change affect ecosystems through short‐term pulse events, such as heatwaves, and chronic long‐term shifts. Temperate rocky reef ecosystems have been observed to show substantial ecological change as a result of short‐term temperature fluctuations, but the longer‐term impacts of temperature change remain poorly understood. Here, we investigate temperate reef fishes and mobile invertebrates along Tasmania's east coast, contrasting trends in species richness, abundance, and community structure across seasons within a year to those observed over three decades of warming. Fishes exhibited dynamic seasonal shifts, but interannual changes in richness and abundance balanced out over decades with limited overall net change. In contrast, invertebrate communities changed little seasonally but suffered significant long‐term losses. Our study revealed short‐term ecological changes driven by temperature to be incongruent with long‐term shifts. Species responded in varying ways, depending on life history and ecology. Fishes apparently tracked short temperature pulses, while less mobile invertebrates, such as echinoderms and molluscs, tolerated short‐term fluctuations but exhibited long‐term decline. Multi‐scale studies across a broad range of taxa are needed to clarify thermal responses. The most vulnerable taxa—those facing long‐term thermal stress—may be overlooked through decisions based on short‐term studies, risking major biodiversity loss.

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Plant metabolic responses to soil herbicide residues differ under herbivory in two woodland strawberry genotypes - Benjamin Fuchs; Marjo Helander; Kari Saikkonen; Petre I. Dobrev; Radomira Vankova; James D. Blande; Juha-Pekka Salminen; Niko Luntamo; Anne Muola (Science of The Total Environment, 2024)

Long sediment-laden algal turf likely impairs coral recovery on Florida’s coral reefs - A. Duran; K. E. Speare; C. Fuchs; T. C. Adam; L. Palma; M. W. Miller; L. Collado-Vides; A. R. Harborne; D. E. Burkepile (Coral Reefs, 2024)

Impacts of irregularly-distributed acidified brine flow on geo-chemo-mechanical alteration in an artificial shale fracture under differential stress - Samantha J. Fuchs; Dustin Crandall; Johnathan E. Moore; Mayandi Sivaguru; Bruce W. Fouke; D. Nicolas Espinoza; Ange-Therese Akono; Charles J. Werth (International Journal of Greenhouse Gas Control, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Toxic elements in arctic and sub-arctic brown bears: Blood concentrations of As, Cd, Hg and Pb in relation to diet, age, and human footprint - Boris Fuchs; Kyle Joly; Grant V. Hilderbrand; Alina L. Evans; Ilia Rodushkin; Lindsey S. Mangipane; Buck A. Mangipane; David D. Gustine; Andreas Zedrosser; Ludovick Brown; Jon M. Arnemo (Environmental Research, 2023)

Making protected areas effective for biodiversity, climate and food - Almut Arneth; Paul Leadley; Joachim Claudet; Marta Coll; Carlo Rondinini; Mark D. A. Rounsevell; Yunne‐Jai Shin; Peter Alexander; Richard Fuchs (Global Change Biology, 2023)
The spatial extent of marine and terrestrial protected areas (PAs) was among the most intensely debated issues prior to the decision about the post‐2020 Global Biodiversity Framework (GBF) of the Convention on Biological Diversity. Positive impacts of PAs on habitats, species diversity and abundance are well documented. Yet, biodiversity loss continues unabated despite efforts to protect 17% of land and 10% of the oceans by 2020. This casts doubt on whether extending PAs to 30%, the agreed target in the Kunming‐Montreal GBF, will indeed achieve meaningful biodiversity benefits. Critically, the focus on area coverage obscures the importance of PA effectiveness and overlooks concerns about the impact of PAs on other sustainability objectives. We propose a simple means of assessing and visualising the complex relationships between PA area coverage and effectiveness and their effects on biodiversity conservation, nature‐based climate mitigation and food production. Our analysis illustrates how achieving a 30% PA global target could be beneficial for biodiversity and climate. It also highlights important caveats: (i) achieving lofty area coverage objectives alone will be of little benefit without concomitant improvements in effectiveness, (ii) trade‐offs with food production particularly for high levels of coverage and effectiveness are likely and (iii) important differences in terrestrial and marine systems need to be recognized when setting and implementing PA targets. The CBD's call for a significant increase in PA will need to be accompanied by clear PA effectiveness goals to reduce and revert dangerous anthropogenic impacts on socio‐ecological systems and biodiversity.

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Overcoming the matrix effect in the element analysis of steel: Laser ablation-spark discharge-optical emission spectroscopy (LA-SD-OES) and Laser-induced breakdown spectroscopy (LIBS) - Stefan Grünberger; Valentin Ehrentraut; Simon Eschlböck-Fuchs; Josef Hofstadler; Andreas Pissenberger; Johannes D. Pedarnig (Analytica Chimica Acta, 2023)

Correction to: Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Correction to: Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Hypericum perforatum L. commonly known as Saint John’s Wort (SJW) is an economically important medicinal plant known for accumulating its valuable bioactive compounds in a compartmentalized fashion. The dark glands are very rich in hypericin, and translucent glands are filled with hyperforin. The antibiotic properties of the afore mentioned bioactive compounds make it hard to establish tissue regeneration protocols essential to put in place a transformation platform that is required for testing gene function in this challenging species. In this study, we report the establishment of a regeneration and root induction cycle from different types of explants. The regeneration cycle was set up for the continuous supply of roots and leaf explants for downstream transformation experiments. The most effective medium to obtain multiple shoot-buds from node cultures was MS (Murashige and Skoog, Physiol Plant 15:473–497, 1962) medium supplemented with 0.5 mg L −1 6-Benzylaminopurine (BAP) and 0.5 mg L −1 indole-3-butyric acid (IBA). The same combination yielded copious amounts of shoots from root and leaf explants as well. For rooting the elongated shoots, MS medium devoid of plant growth regulators (PGRs) was sufficient. Nevertheless, addition of a low amount of IBA improved the quantity and quality of roots induced. Additionally, the roots obtained on a medium containing IBA readily developed shoot buds.

Characterizing U.S. drought over the past 20 years using the U.S. drought monitor - Ronald D. Leeper; Rocky Bilotta; Bryan Petersen; Crystal J. Stiles; Richard Heim; Brian Fuchs; Olivier P. Prat; Michael Palecki; Steve Ansari (International Journal of Climatology, 2022)
The main challenge of evaluating droughts in the context of climate change and linking these droughts to adverse societal outcomes is a lack of a uniform definition that identifies drought conditions at a location and time. The U.S. Drought Monitor (USDM), created in 1999, is a well‐established composite index that combines drought indicators across the hydrological cycle (i.e., meteorological to hydrological) with information from local experts. This makes the USDM one of the most holistic measures for evaluating past drought conditions across the United States. In this study, the USDM was used to define drought events as consecutive periods in time where the USDM status met or exceeded D1 conditions over the past 20 years. This analysis was applied to 5 km grid cells covering the U.S. and Puerto Rico to characterize the frequency, duration, and intensification rates of drought, and the timing of onset, amelioration, and other measures for every drought event on record. Results from this analysis revealed stark contrasts in the evolution of drought across the United States. Over the western United States, droughts evolved much slower, resulting in longer‐lasting but fewer droughts. The eastern United States experienced more frequent, shorter‐duration events. Given the slower evolution from onset to drought peak, flash droughts, which made up 9.8% of all droughts, were less common across the western United States, with a greater frequency over the southern United States. The most severe drought event on record was the 2012 drought, when more than 21% of the United States experienced its largest number of weeks at or above extreme (D3) drought conditions. The availability of historical drought events would support future societal impacts studies relating drought to adverse outcomes and aid in the evaluation of mitigation strategies by providing a dataset to local decision makers to compare and evaluate past droughts.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Phylogeography of a widespread Palaearctic forest bird species: The White‐backed Woodpecker (Aves, Picidae) - Jean‐Marc Pons; David Campión; Giorgio Chiozzi; Antonia Ettwein; Jean‐Louis Grangé; Łukasz Kajtoch; Tomasz D. Mazgajski; Marko Rakovic; Hans Winkler; Jérôme Fuchs (Zoologica Scripta, 2021)
We use multilocus molecular data and species distribution modelling to investigate the phylogenetics and the phylogeography of the White‐backed Woodpecker ( Dendrocopos leucotos ), a bird species widely distributed over the entire Palaearctic. Our phylogenetic results reveal three well‐supported clades within D. leucotos : the Chinese endemic subspecies ( tangi , insularis ), the northerly distributed subspecies ( leucotos , uralensis ) and the four poorly genetically differentiated Japanese subspecies ( subcirris , stejnegeri , namiyei, owstoni ), and the south‐western Palaearctic lilfordi subspecies. According to our results, the Amami Woodpecker, endemic to Amami Oshima Island (Ryukyu archipelago, Japan) sometimes treated as full species Dendrocopos owstoni , does not deserve a species‐level status. Based on the mitochondrial phylogeographic results, the Japanese archipelago was recently colonized only once by D. leucotos from eastern Eurasia. Our results suggest a split between the leucotos and lilfordi lineages that dates back to mid‐Pleistocene (around 0.6 Mya) with likely no gene flow between these two subspecies since then. Our results thus do not support a phylogeographic pattern in which Central Europe and Northern Europe were recolonized from one or several southern glacial refugia where lilfordi populations persisted through several Pleistocene glacial periods. Spatial variation in mitochondrial diversity across leucotos/uralensis populations and niche ecological modelling suggest a possible eastward population expansion from a unique glacial refugium likely located in Central Europe. Molecular species delimitation methods, gene flow analyses and differences in adult and juvenile plumage indicate that the lilfordi subspecies may warrant to be ranked as a valid phylogenetic species. Further studies are nevertheless needed in the Balkans, where leucotos and lilfordi came recently into contact to measure the effectiveness of reproductive barriers and gene flow.

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Divining gold in seafloor polymetallic massive sulfide systems - Sebastian Fuchs; Mark D. Hannington; Sven Petersen (Mineralium Deposita, 2019)

Tryptophan-kynurenine profile in pediatric autoimmune hepatitis - Simon D. Lytton; Marcin Osiecki; MałgorzataWoźniak; Bożena Cukrowska; Aldona Wierzbicka; Maria Goliszek; Piotr Socha; Wojciech Janczyk; Dilek Dayanakli; Dieter Abendroth; Sabine Kramp; Kai Fechner; et al. (Immunologic Research, 2019)

Influence of immunostimulant polysaccharides, nucleic acids, and Bacillus strains on the innate immune and acute stress response in turbots (Scophthalmus maximus) fed soy bean- and wheat-based diets - V. I. Fuchs; J. Schmidt; M. J. Slater; B. H. Buck; D. Steinhagen (Fish Physiology and Biochemistry, 2017)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

A bibliometric-based evaluation on environmental research in the Arab world - SH. H. Zyoud; D. Fuchs-Hanusch; S. H. Zyoud; A. E. Al-Rawajfeh; H. Q. Shaheen (International Journal of Environmental Science and Technology, 2017)

Land management: data availability and process understanding for global change studies - Karl‐Heinz Erb; Sebastiaan Luyssaert; Patrick Meyfroidt; Julia Pongratz; Axel Don; Silvia Kloster; Tobias Kuemmerle; Tamara Fetzel; Richard Fuchs; Martin Herold; Helmut Haberl; Chris D. Jones; et al. (Global Change Biology, 2017)
In the light of daunting global sustainability challenges such as climate change, biodiversity loss and food security, improving our understanding of the complex dynamics of the Earth system is crucial. However, large knowledge gaps related to the effects of land management persist, in particular those human‐induced changes in terrestrial ecosystems that do not result in land‐cover conversions. Here, we review the current state of knowledge of ten common land management activities for their biogeochemical and biophysical impacts, the level of process understanding and data availability. Our review shows that ca. one‐tenth of the ice‐free land surface is under intense human management, half under medium and one‐fifth under extensive management. Based on our review, we cluster these ten management activities into three groups: (i) management activities for which data sets are available, and for which a good knowledge base exists (cropland harvest and irrigation); (ii) management activities for which sufficient knowledge on biogeochemical and biophysical effects exists but robust global data sets are lacking (forest harvest, tree species selection, grazing and mowing harvest, N fertilization); and (iii) land management practices with severe data gaps concomitant with an unsatisfactory level of process understanding (crop species selection, artificial wetland drainage, tillage and fire management and crop residue management, an element of crop harvest). Although we identify multiple impediments to progress, we conclude that the current status of process understanding and data availability is sufficient to advance with incorporating management in, for example, Earth system or dynamic vegetation models in order to provide a systematic assessment of their role in the Earth system. This review contributes to a strategic prioritization of research efforts across multiple disciplines, including land system research, ecological research and Earth system modelling.

Sensory feedback in cockroach locomotion: current knowledge and open questions - A. Ayali; E. Couzin-Fuchs; I. David; O. Gal; P. Holmes; D. Knebel (Journal of Comparative Physiology A, 2015)

Approach to Cerebrospinal Fluid (CSF) Biomarker Discovery and Evaluation in HIV Infection - Richard W. Price; Julia Peterson; Dietmar Fuchs; Thomas E. Angel; Henrik Zetterberg; Lars Hagberg; Serena Spudich; Richard D. Smith; Jon M. Jacobs; Joseph N. Brown; Magnus Gisslen (Journal of Neuroimmune Pharmacology, 2013)

Rediscovering ACE: novel insights into the many roles of the angiotensin-converting enzyme - Romer A. Gonzalez-Villalobos; Xiao Z. Shen; Ellen A. Bernstein; Tea Janjulia; Brian Taylor; Jorge F. Giani; Wendell-Lamar B. Blackwell; Kandarp H. Shah; Peng D. Shi; Sebastien Fuchs; Kenneth E. Bernstein (Journal of Molecular Medicine, 2013)

Mouse large-scale phenotyping initiatives: overview of the European Mouse Disease Clinic (EUMODIC) and of the Wellcome Trust Sanger Institute Mouse Genetics Project - Abdel Ayadi; Marie-Christine Birling; Joanna Bottomley; James Bussell; Helmut Fuchs; Martin Fray; Valérie Gailus-Durner; Simon Greenaway; Richard Houghton; Natasha Karp; Sophie Leblanc; Christoph Lengger; et al. (Mammalian Genome, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

In vitro testing for anti-inflammatory properties of compounds employing peripheral blood mononuclear cells freshly isolated from healthy donors - M. Jenny; M. Klieber; D. Zaknun; S. Schroecksnadel; K. Kurz; M. Ledochowski; H. Schennach; Dietmar Fuchs (Inflammation Research, 2011)

Morphology, testes development and behaviour of unusual triploid males in microchromosome‐carrying clones of Poecilia formosa - D. K. Lamatsch; M. Stöck; R. Fuchs; M. Döbler; R. Wacker; J. Parzefall; I. Schlupp; M. Schartl (Journal of Fish Biology, 2010)
In a microchromosome‐carrying laboratory stock of the normally all‐female Amazon molly Poecilia formosa triploid individuals were obtained, all of which spontaneously developed into males. A comparison of morphology of the external and internal insemination apparatus and the gonads, sperm ploidy and behaviour, to laboratory‐bred F 1 hybrids revealed that the triploid P. formosa males, though producing mostly aneuploid sperm, are partly functional males that differ mainly in sperm maturation and sexual motivation from gonochoristic P. formosa males.

New insights into the role of angiotensin-converting enzyme obtained from the analysis of genetically modified mice - Xiao Z. Shen; Hong D. Xiao; Ping Li; Chentao X. Lin; Sandrine Billet; Derick Okwan-Duodu; Jon W. Adams; Ellen A. Bernstein; Yi Xu; Sebastien Fuchs; Kenneth E. Bernstein (Journal of Molecular Medicine, 2008)

Improvement and application of the biocontrol fungus Stagonospora convolvuli LA39 formulation for efficient control of Calystegia sepium and Convolvulus arvensis - D. Boss; E. Schläpfer; J. Fuchs; G. Défago; M. Maurhofer (Journal of Plant Diseases and Protection, 2007)

Adverse events of blood-pressure-lowering drugs: evidence of high incidence in a clinical setting - Carla B.C. Gonçalves; Leila B. Moreira; Miguel Gus; Flávio D. Fuchs (European Journal of Clinical Pharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Exploring the method of optical dating and comparison of optical and 14 C ages of Late Weichselian coversands in the southern Netherlands - D. Vandenberghe; C. Kasse; S. M. Hossain; F. De Corte; P. Van Den Haute; M. Fuchs; A. S. Murray (Journal of Quaternary Science, 2004)
A study was made of the applicability of three different techniques for equivalent dose ( D e ) determination in the optical dating of quartz: the single‐aliquot regenerative‐dose technique (SAR), the single‐aliquot additive‐dose technique (SAAD) and the multiple‐aliquot additive‐dose technique (MAAD). For this purpose, quartz grains were extracted from a sequence of Upper Pleniglacial to Late‐glacial coversands exposed at the locality of Ossendrecht in the southwestern Netherlands, a site for which both radiocarbon and earlier luminescence dates are available, providing independent age control. Upon testing the different assumptions underlying each of the three OSL techniques investigated, the SAR protocol was found to be the technique of choice. The optical ages obtained with this protocol were in good agreement with the chronostratigraphical position of the sediments investigated and with the available chronostratigraphical information on the same and equivalent deposits. This confirms the suitability of the SAR technique for dating coversands. Furthermore, a small laboratory intercomparison of SAR‐based D e determinations yielded results that were in fair overall agreement. Copyright © 2004 John Wiley & Sons, Ltd.

Potential role of immune system activation-associated production of neopterin derivatives in humans - G. Hoffmann; B. Wirleitner; D. Fuchs (Inflammation Research, 2003)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Linking the composition of bacterioplankton to rapid turnover of dissolved dimethylsulphoniopropionate in an algal bloom in the North Sea - Mikhail V. Zubkov; Bernhard M. Fuchs; Stephen D. Archer; Ronald P. Kiene; Rudolf Amann; Peter H. Burkill (Environmental Microbiology, 2001)
The algal osmolyte, dimethylsulphoniopropionate (DMSP), is abundant in the surface oceans and is the major precursor of dimethyl sulphide (DMS), a gas involved in global climate regulation. Here, we report results from an in situ Lagrangian study that suggests a link between the microbially driven fluxes of dissolved DMSP (DMSPd) and specific members of the bacterioplankton community in a North Sea coccolithophore bloom. The bacterial population in the bloom was dominated by a single species related to the genus Roseobacter , which accounted for 24% of the bacterioplankton numbers and up to 50% of the biomass. The abundance of the Roseobacter cells showed significant paired correlation with DMSPd consumption and bacterioplankton production, whereas abundances of other bacteria did not. Consumed DMSPd (28 nM day −1 ) contributed 95% of the sulphur and up to 15% of the carbon demand of the total bacterial populations, suggesting the importance of DMSP as a substrate for the Roseobacter ‐dominated bacterioplankton. In dominating DMSPd flux, the Roseobacter species may exert a major control on DMS production. DMSPd turnover rate was 10 times that of DMS (2.7 nM day −1 ), indicating that DMSPd was probably the major source of DMS, but that most of the DMSPd was metabolized without DMS production. Our study suggests that single species of bacterioplankton may at times be important in metabolizing DMSP and regulating the generation of DMS in the sea.

Increased blood-brain barrier permeability in neuro-asymptomatic HIV-1-infected individualscorrelation with cerebrospinal fluid HIV-1 RNA and neopterin levels - L M Andersson, L Hagberg, D Fuchs, B (Journal of NeuroVirology, 2001)

A 500-kb region on chromosome 16p13.1 contains the pseudoxanthoma elasticum locus: high-resolution mapping and genomic structure - Li Cai; Berthold Struk; Mark D. Adams; Wan Ji; Thomas Haaf; Hyung-Lyun Kang; So Hee Dho; Xuequn Xu; Franziska Ringpfeil; Julie Nancarrow; Stéphanie Zäch; Lori Schaen; et al. (Journal of Molecular Medicine, 2000)

Lack of Effect of Antibiotic Resistance on Susceptibility of Microorganisms to Chlorhexidine Gluconate or Povidone Iodine - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Antibacterial Activity of Moxifloxacin (Bay 12-8039) against Aerobic Clinical Isolates, and Provisional Criteria for Disk Susceptibility Tests - S. D. Brown; A. L. Barry; P. C. Fuchs (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Differential effects of 7-OH-DPAT on amphetamine-induced stereotypy and conditioned place preference - T. V. Khroyan; D. A. Baker; R. A. Fuchs; N. Manders; J. L. Neisewander (Psychopharmacology, 1998)

Uptake of poliovirus into the endosomal system of HeLa cells - P. Kronenberger; D. Schober; E. Prchla; O. Ofori-Anyinam; R. Vrijsen; B. Rombaut; D. Blaas; R. Fuchs; A. Boeyé (Archives of Virology, 1998)

Properties of Advanced Headmodelling and Source Reconstruction for the Localization of Epileptiform Activity - Till D. Waberski; Helmut Buchner; Klaus Lehnertz; Andreas Hufnagel; Manfred Fuchs; Rainer Beckmann; Adrian Rienäcker (Brain Topography, 1998)

In vitro activity of the new ketolide HMR 3004 compared to an azalide and macrolides againstStreptococcus pneumoniae andHaemophilus influenzae - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Susceptibility testing quality control studies with fosfomycin tromethamine - P. C. Fuchs; A. L. Barry; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

In vitro activity of an orally administered streptogramin (RPR 106,972) compared to quinupristin/dalfopristin and erythromycin - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Acetate oxidation to CO2 via a citric acid cycle involving an ATP-citrate lyase: a mechanism for the synthesis of ATP via substrate level phosphorylation in Desulfobacter postgatei growing on acetate and sulfate - D. Mller; R. Schauder; G. Fuchs; R. K. Thauer (Archives of Microbiology, 1987)

Die Ultrastruktur des Penetrationsvorganges von Olpidium brassicae an Kohlrabi-Wurzeln - D. E. Lesemann; W. H. Fuchs (Archives of Microbiology, 1970)

Elektronenmikroskopische Untersuchung ber die Vorbereitung der Infektion in encystierten Zoosporen von Olpidium brassicae - D. E. Lesemann; W. H. Fuchs (Archives of Microbiology, 1970)